2010
DOI: 10.1634/theoncologist.2010-0029
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Soluble VEGFR-1 Is a Potential Dual Biomarker of Response and Toxicity for Bevacizumab with Chemoradiation in Locally Advanced Rectal Cancer

Abstract: We explored plasma and urinary concentrations of two members of the vascular endothelial growth factor (VEGF) family and their receptors as potential response and toxicity biomarkers of bevacizumab with neoadjuvant chemoradiation in patients with localized rectal cancer. The concentrations of VEGF, placental growth factor (PlGF), soluble VEGF receptor 1 (sVEGFR-1), and sVEGFR-2 were measured in plasma and urine at baseline and during treatment. Pretreatment values and changes over time were analyzed as potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 25 publications
7
59
0
1
Order By: Relevance
“…We and others have demonstrated that anti-VEGFR therapy is invariably associated with increases in PlGF and decreases in plasma sVEGFR2 across different anti-VEGF tyrosine kinase inhibitors (e.g. cediranib, sorafenib, vandetanib, sunitinib) and different cancers (10,(31)(32)(33)(34)(35)(36). Thus, data from our study support the notion that PlGF and sVEGFR2 should be further explored as pharmacodynamic biomarkers (i.e., surrogate biomarkers of biological activity).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We and others have demonstrated that anti-VEGFR therapy is invariably associated with increases in PlGF and decreases in plasma sVEGFR2 across different anti-VEGF tyrosine kinase inhibitors (e.g. cediranib, sorafenib, vandetanib, sunitinib) and different cancers (10,(31)(32)(33)(34)(35)(36). Thus, data from our study support the notion that PlGF and sVEGFR2 should be further explored as pharmacodynamic biomarkers (i.e., surrogate biomarkers of biological activity).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, consistent with the results from a study of cediranib in rGBM (10), we detected an association between sVEGFR1 levels after 4 wk of treatment and PFS after cediranib/chemoradiation in nGBM. We previously proposed that sVEGFR1-a negative regulator of the VEGF pathway-is a potential resistance biomarker to anti-VEGF therapy (31). However, because cediranib significantly decreases sVEGFR1 levels in circulation, future studies should determine if the associations observed are because of the biological effects of sVEGFR1 or because of "pharmacodynamic" changes in its level as a result of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation is consistent with the reported anti-angiogenic activity of sVEGFR-2 and inhibition of xenograft tumor growth by gene therapy with soluble sVEGFR-1, -2, and -3 [24][25][26]. While some studies reported correlations of high sVEGFR status with poorer prognosis of cancer patients [27][28][29], studies which evaluated the ratio of sVEGFR-1 to sVEGF reported that low sVEGFR-1 associated with high VEGF was associated with poorer prognosis [30,31]. The association of high IGFBP1 levels with worse survival is consistent with published studies of mortality in older adults [32,33].…”
Section: Discussionsupporting
confidence: 87%
“…In metastatic breast cancer, genetic polymorphisms of the VEGFR1 and VEGFR2 may be associated with the clinical prognosis (Schneider et al, 2008). In rectal cancer, the circulating soluble VEGFR1 (sVEGFR1) is suggested to be a predictor of survival performance in neoadjuvant treatment with bevacizumab-containing radiochemotherapy (Duda et al, 2010). Furthermore, some evidence exists concerning a prognostic significance of circulating endothelial cells reflecting active angiogenesis (Ronzoni et al, 2010).…”
Section: From Bench To Clinic and Vice Versa -Unanticipated Lessons Fmentioning
confidence: 99%